A Multiscale In Silico Study to Characterize the Atrial Electrical Activity of Patients With Atrial Fibrillation A Translational Study to Guide Ablation Therapy - Patricio Sánchez Arciniegas, Jorge (Karlsruhe transactions on biomedical engineering, 2022)
The atrial substrate undergoes electrical and structural remodeling during atrial fibrillation. Detailed multiscale models were used to study the effect of structural remodeling induced at the cellular and tissue levels. Simulated electrograms were used to train a machine-learning algorithm to characterize the substrate. Also, wave propagation direction was tracked from unannotated electrograms. In conclusion, in silico experiments provide insight into electrograms' information of the substrate.